PROFITABILITAS SEBAGAI MEDIASI UKURAN PERUSAHAAN, LDR DAN NPL DENGAN NILAI PERUSAHAAN - Dwi Danesty Deccasari; Dheva Novianda Saputri; Marli Marli (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This research was conducted to examine the effect of firm size, Loan to Deposit Ratio and Non-Performing Loans on Firm Value with Profitability as an intervening variable. This study uses data from 41 banking companies on the Indonesia Stock Exchange with a purposive sampling technique. Quantitative research methods using PLS SEM with SmartPLS. The results of the study stated that company size and Loan to Deposit Ratio had a significant positive effect on profitability, and Non Performing Loans had a significant negative effect on profitability. Firm size, loan to deposit ratio and non-performing loans do not have a direct effect on firm value, and profitability has a significant effect on firm value. Profitability can mediate the effect of company size and loan to deposit ratio on firm value, but non-performing loans are not mediated by profitability on firm value.